(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The wood of deciduous species are characterized by complex structure and greater specialization of cells. Besides the different diameter and density for each type trachea may be more or less similar in size. The work examines the differences of the trachea in several mestnorastyashti several tropical tree species. Measured are the dimensions of cells and their variation within the annual ring. Certain cells are area variances and their diameter. Comparison is made between anatomical characteristics of individual species.